2017
DOI: 10.1016/j.addbeh.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Treatment non-response: Associations with smoking expectancies among treatment-seeking smokers

Abstract: Despite the high rate of smoking cessation treatment non-response, relatively little empirical work has examined predictors of treatment non-response. The present study sought to explore the effect of smoking outcome expectancies on treatment response in a sample of treatment-seeking adult daily smokers (N = 182; 53.3% female; Mage = 40.67; SD = 13.63). Results indicated that expectancies for smoking to reduce negative affect were related to an increased likelihood of treatment non-response (OR = 0.73, CI: 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…18,19 Yet, individuals in smoking cessation programs who reported greater amounts of positive outcome expectancies were associated with decreased cigarette abstinence. 13,15 While the physical, mental, and financial benefits of smoking cessation may be easy to recognize, recognizing the malignant metabolic effects of smoking cessation are just as critical. These include post-cessation weight gain mediated insulin resistance, placing one at risk for diabetes and cardiovascular disease and making cessation difficult.…”
Section: Expectancies In Treatment Outcomesmentioning
confidence: 99%
“…18,19 Yet, individuals in smoking cessation programs who reported greater amounts of positive outcome expectancies were associated with decreased cigarette abstinence. 13,15 While the physical, mental, and financial benefits of smoking cessation may be easy to recognize, recognizing the malignant metabolic effects of smoking cessation are just as critical. These include post-cessation weight gain mediated insulin resistance, placing one at risk for diabetes and cardiovascular disease and making cessation difficult.…”
Section: Expectancies In Treatment Outcomesmentioning
confidence: 99%
“…The students believe that smoking helps them to adapt to the physical, cognitive, and emotional changes that are taking place, although various studies have proved that smoking reduces self-esteem and self-image among those with severe addiction [14]. A previous study also showed that smoking addiction is associated with depression; but adolescents perceived that smoking could eliminate their negative feelings, and this perception was one of the risk factors for failure in a cessation program [15]. A previous report also found that teenagers are vulnerable to negative social in uences from commercial groups that promote cigarettes, and therefore building their self-con dence is crucial to reduce vulnerability [4].…”
Section: Introductionmentioning
confidence: 99%
“…The students believe that smoking helps them to adapt to the physical, cognitive, and emotional changes that are taking place, although various studies have proved that smoking reduces self-esteem and self-image among those with severe addiction [14]. A previous study also showed that smoking addiction is associated with depression; but adolescents perceived that smoking could eliminate their negative feelings, and this perception was one of the risk factors for failure in a cessation program [15]. A previous report also found that teenagers are vulnerable to negative social in uences from commercial groups that promote cigarettes, and therefore building their self-con dence is crucial to reduce vulnerability [4].…”
Section: Introductionmentioning
confidence: 99%